Addressing Obesity Through Homeopathy (Advancements in Homeopathic Research, 2025)
The word ‘Obesity’ came from Latin word; where the  verb ‘obedere’ means ‘over eat’ and ‘obesitas’ means  ‘being very fat’. Obesity is a health condition in which the natural  energy stored, reserved in the fatty tissue of human  beings, is increased to that point where it is linked  with certain health issues. It can be defined in  relative or absolute terms. Practically, it is evaluated  in absolute terms by measuring BMI (body mass  index), but also in terms of its distribution through  waist circumference or waist-hip circumference  ratio measurements. The normal amount of body  fat (expressed as percentage of body fat) is between  26-30% in female and 19-24% in male. Female with  over 30% body fat and male with over 25% body fat  are considered as obese. Women of reproductive age have higher rates of  overweight and obesity and are more adversely  affected by obesity-related complications than men.  This gender difference is mainly due to general  weight gain during childbearing years, gestational  weight gain and weight retention, adverse lifestyle,  or risk factors associated with pregnancy and the  postpartum period. Maternal obesity increases the  risk of numerous complications including pregnancy,  labour and birth for both the mother and the child,  diabetes and hypertensive disorders etc. Compared  with normal weight, maternal overweight is  associated with a higher risk of caesarean delivery and  a higher incidence of anaesthetic and postoperative  complications. Low Apgar scores, macrosomia and  neural tube defects are also more frequent in infants  of obese mothers compared with infants of normal weight mothers.  Obesity may be caused by a number of social,  cultural, behavioral, physiological, metabolic, and  genetic factors that are beyond the person's control.  Obesity is most commonly caused by a combination  of excessive food energy intake, lack of physical  activity, and genetic susceptibility, although a few  cases are caused primarily by genes, endocrine  disorders, medications or psychiatric illness. It is  associated with increased risk of medical illness,  disability, and death. It is a metabolic disorder  that is primarily induced and sustained by an  over consumption and underutilization of caloric  substrate.
Keywords: Obesity; obedere; over eat; obesitas; being very fat